PENGEMBANGAN KURIKULUM DAN DAMPAKNYA TERHADAP PENDIDIKAN AGAMA ISLAM PADA MATERI ZAKAT DI SD ISLAM BABUR- RIDHO JAKARTA UTARA - Baihaki Baihaki (el-Moona: Jurnal Ilmu Pendidikan Islam, 2020)
This thesis is the Conclusion: Development of Kurikulumdan impact on Islamic education material on zakat the Islamic primary school Baburridho Cilincing in North Jakarta. Education is a very important basic needs for the people Currently, Indonesia society to meet these then needed an institution as a buffer, a dealer in developing science for learners. In this case it is a school. In the school there are plans, ideas that will be applied and implemented in peroses learning with curriculum. Curriculum policy in determining the success of Indoenesia considered an education. Therefore, Indonesia experienced several times in rapid succession the curriculum. The curriculum is flexible and adapts to the times community surroundings. One of them, namely the curriculum that proclaimed the Islamic primary school Baburridho in Cilincing, Jakarta Utara. Aspects that became the focus of the research is the development of Islamic religious education curriculum content in elementary school Islamic zakat Baburridho Cilincing, Jakarta North. This research, qualitative research is descriptive, namely data collection dilakuakan through observation, interviews, and documentation. Qualitative data were analyzed in a descriptive analytic through three stages, namely the reduction of data, data presentation, and conclusion/verification. The results showed that: first, Islamic primary school Baburridho Cilincing Jakarta North using two educational curriculum for Islamic Curriculum, namely agam unit level education (KTSP) applied in class II, III, V, and VI, and curriculum 2013 applied in class I and IV. Second, in Islamic Studies Curriculum document that contains material zakat is in class VI semester II. Administratively, for Islamic primary school learning supplies Baburridho Cilincing Jakarta North follows the rules defined by the Ministry of national education. In Islamic education curriculum documents are applied in the school, especially in material zakat is not the case. However, as a practitioner, have the development and impact of broader knowledge against students. So, learners are able to memperaktekan material melafal and writing nelalui zakat intent issued and receive zakat fitrah zakat Committee and memperaktekan be processed.